1992
DOI: 10.1117/12.137385
|View full text |Cite
|
Sign up to set email alerts
|

<title>Hi-tech of the prostate: interstitial laser coagulation of benign prostatic hypertrophy</title>

Abstract: We report on the new technique of interstitial laser coagulation of the prostate (ILCP) in the treatment of benign prostatic hyperplasia (BPH).Basic experiments by use of a Nd:YAG laser in combination with a newly designed fiber tip homogeneously distributing the laser Dependent on the size of the prostate irradiation time was 5 to 10 minutes per lobe at a power setting of 5 to low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 3 publications
(3 reference statements)
0
11
0
2
Order By: Relevance
“…The new concept of minimally invasive BPH treatment developed by our group [14,30] is based on the creation of intraprostatic coagulation lesions. In contrast to any heat treatment where energy from an applicator inside the urethra is delivered to the periurethral prostatic tissue, in interstitial energy delivery the urethra would not be affected.…”
mentioning
confidence: 99%
“…The new concept of minimally invasive BPH treatment developed by our group [14,30] is based on the creation of intraprostatic coagulation lesions. In contrast to any heat treatment where energy from an applicator inside the urethra is delivered to the periurethral prostatic tissue, in interstitial energy delivery the urethra would not be affected.…”
mentioning
confidence: 99%
“…7,8,[11][12][13] The in vitro studies in muscle, liver, kidney, and the potato models showed that treatment volumes increased with la ser power and irradiation time unless charring oc- …”
mentioning
confidence: 99%
“…Both neodymium: yttrium-aluminum-garnet (Nd:YAG) laser (1,064 nm) and diode laser (800 -1,000 nm) energies are used for interstitial laser coagulation because of their relatively deep penetration in water, efficient volumetric tissue heat loading, and ability to be delivered through flexible optical fibers (see also table 1 for details). 1,2 The optimal irradiation parameters vary for different laser wavelength and applicator combinations. 2,3,4 The goal of creating the largest coagulative volume in the shortest surgical time is accomplished by initiating irradiation with a relatively high power to heat the tissue rapidly and coagulate the blood vessels, followed by reduction of laser power to maintain the temperature in the center of the lesion at a high level just below the carbonization threshold and allow further expansion of the lesion.…”
Section: Introductionmentioning
confidence: 99%